The Macrophage Switch in Obesity Development - Castoldi, Angela; Naffah de Souza, Cristiane; Câmara, Niels Olsen Saraiva; Moraes-Vieira, Pedro M. (Frontiers in Immunology, 2016)
Immune cell infiltration in (white) adipose tissue during obesity is associated with the development of insulin resistance. In adipose tissue, the main population of leukocytes are macrophages. Macrophages can be classified into two major populations: M1, classically activated macrophages, and M2, alternatively activated macrophages, although recent studies have identified a broad range of macrophage subsets. During obesity, adipose tissue M1 macrophage numbers increase and correlate with adipose tissue inflammation and insulin resistance. Upon activation, pro-inflammatory M1 macrophages induce aerobic glycolysis. By contrast, in lean humans and mice, the number of M2 macrophages predominates. M2 macrophages secrete anti-inflammatory cytokines and utilize oxidative metabolism to maintain adipose tissue homeostasis. Here we review the immunologic and metabolic functions of adipose tissue macrophages and their different facets in obesity and the metabolic syndrome.